2018
DOI: 10.1002/wdev.324
|View full text |Cite
|
Sign up to set email alerts
|

Talking back: Development of the olivocochlear efferent system

Abstract: Developing sensory systems must coordinate the growth of neural circuitry spanning from receptors in the peripheral nervous system (PNS) to multilayered networks within the central nervous system (CNS). This breadth presents particular challenges, as nascent processes must navigate across the CNS-PNS boundary and coalesce into a tightly intermingled wiring pattern, thereby enabling reliable integration from the PNS to the CNS and back. In the auditory system, feedforward spiral ganglion neurons (SGNs) from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 240 publications
(386 reference statements)
2
32
0
Order By: Relevance
“…Without the MOC-mediated mechanism that we identified, uncoupled streams of peripheral activity might decrease synchronous activity between presynaptic crossing fibers and postsynaptic auditory neurons, thus undermining bilateral circuit maturation. Moreover, the MOC-mediated bilateral coupling is itself tonotopic, consistent with the known efferent innervation pattern (Frank and Goodrich, 2018). Therefore, the MOC-mediated cochlea coupling can serve as a neural substrate that mimics the bilateral features of real-world stimuli and promotes Hebbian plasticity across two sides of the auditory system.…”
Section: Novel Aspect Of Efferent Modulation In Patterning Auditory Ssupporting
confidence: 60%
See 1 more Smart Citation
“…Without the MOC-mediated mechanism that we identified, uncoupled streams of peripheral activity might decrease synchronous activity between presynaptic crossing fibers and postsynaptic auditory neurons, thus undermining bilateral circuit maturation. Moreover, the MOC-mediated bilateral coupling is itself tonotopic, consistent with the known efferent innervation pattern (Frank and Goodrich, 2018). Therefore, the MOC-mediated cochlea coupling can serve as a neural substrate that mimics the bilateral features of real-world stimuli and promotes Hebbian plasticity across two sides of the auditory system.…”
Section: Novel Aspect Of Efferent Modulation In Patterning Auditory Ssupporting
confidence: 60%
“…Our results revealed a changing profile of in vivo spontaneous activity and evolving bilateral connectivity in the auditory system that peaks early in the pre-hearing period and slowly declines prior to hearing onset. Intriguingly, the strength of bilateral coupling matched the time course of a transient cholinergic modulation imposed on inner hair cells by the medial-olivocochlear (MOC) efferent system (Katz et al, 2004, Elgoyhen and Katz, 2012, Kearney et al, 2019, Frank and Goodrich, 2018. Mice lacking the a9/a10 nicotinic acetylcholine receptor (nAChR), a necessary constituent of efferent modulation (Elgoyhen et al, 1994, Elgoyhen et al, 2001, Morley et al, 2017, displayed severly disrupted bilateral correlations.…”
Section: Introductionmentioning
confidence: 93%
“…And as a fifth event, the type I SGN peripheral processes become innervated by lateral olivocochlear (LOC) efferent axons (Bergeron, Schrader, Yang, Osman, & Simmons, ), which protect against sound‐evoked damage (Darrow et al, ) and may also regulate auditory input (Guinan, ). We note here that the SGNs must also compete for synaptic space on inner hair cells with medial olivocochlear (MOC) efferents, which make transient contacts with inner hair cells before innervating outer hair cells (Frank & Goodrich, ). Studies have shown efferent innervation starting as early as E18.5 in mouse cochleae (Bruce, Kingsley, Nichols, & Fritzsch, ) and soon after birth in rat cochleae (Knipper, Zimmermann, Rohbock, Köpschall, & Zenner, ; Simmons, ).…”
Section: Sgn Development After Birthmentioning
confidence: 99%
“…In both systems, the perception of sensory information depends upon mechanosensory transduction by hair cells (HCs) and the delivery of this information to the primary afferent neurons that make synaptic connections with the receptor cells (Lewis, Leverenz, & Bialek, ). Many research groups have investigated how classic axon guidance factors impact afferent innervation of the auditory and vestibular organs (Appler & Goodrich, ; Battisti, Fantetti, Moyers, & Fekete, ; Coate, Spita, Zhang, Isgrig, & Kelley, ; Defourny et al, ; Fekete & Campero, ; Frank & Goodrich, ; Ghimire, Ratzan, & Deans, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many research groups have investigated how classic axon guidance factors impact afferent innervation of the auditory and vestibular organs (Appler & Goodrich, 2011;Battisti, Fantetti, Moyers, & Fekete, 2014;Coate, Spita, Zhang, Isgrig, & Kelley, 2015;Defourny et al, 2013;Fekete & Campero, 2007;Frank & Goodrich, 2018;Ghimire, Ratzan, & Deans, 2018).…”
Section: Introductionmentioning
confidence: 99%